2012
DOI: 10.1111/j.1600-6143.2011.03786.x
|View full text |Cite
|
Sign up to set email alerts
|

Re-examination of the Lymphocytotoxic Crossmatch in Liver Transplantation: Can C4d Stains Help in Monitoring?

Abstract: C4d-assisted recognition of antibody-mediated rejection (AMR) in formalin-fixed paraffin-embedded tissues (FFPE) from donor-specific antibody-positive (DSA+)renal allograft recipients prompted study of DSA+ liver allograft recipients as measured by lymphocytotoxic crossmatch (XM) and/or Luminex. XM results did not influence patient or allograft survival, or cellular rejection rates, but XM+ recipients received significantly more prophylactic steroids. Endothelial C4d staining strongly correlates with XM+ (<3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 36 publications
3
87
0
2
Order By: Relevance
“…The development of de novo DSAs (with a mean fluorescence intensity > 5000) in 61 recipients (8.1%) was associated with decreased 5-year graft and patient survival in a recent retrospective analysis of 749 adult liver transplant recipients. 33 In a more detailed study of 809 liver transplants from a single center, 23 allograft biopsy samples from cross-match-positive recipients had more histological evidence of biliary duct, portal, and venous subendothelial inflammation. Biopsy samples were obtained more than 3 weeks after transplantation from 9 recipients with persistent circulating DSAs, and ongoing ACR or ischemic cholangitis was found in 7 of them.…”
Section: Human Leukocyte Antigen Antibodies and Graft Injury/ Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of de novo DSAs (with a mean fluorescence intensity > 5000) in 61 recipients (8.1%) was associated with decreased 5-year graft and patient survival in a recent retrospective analysis of 749 adult liver transplant recipients. 33 In a more detailed study of 809 liver transplants from a single center, 23 allograft biopsy samples from cross-match-positive recipients had more histological evidence of biliary duct, portal, and venous subendothelial inflammation. Biopsy samples were obtained more than 3 weeks after transplantation from 9 recipients with persistent circulating DSAs, and ongoing ACR or ischemic cholangitis was found in 7 of them.…”
Section: Human Leukocyte Antigen Antibodies and Graft Injury/ Survivalmentioning
confidence: 99%
“…Diffuse portal C4d staining can be seen in up to two-thirds of biopsy samples with ACR, 21,42 although a recent report demonstrated that there is no difference between cases of ACR with or without diffuse C4d deposition with respect to the Banff grade of rejection or liver enzymes. 23 Several studies have looked at the differences in the location of C4d deposition between DSA-positive and DSA-negative liver transplant recipients. Arterial, portal venous, and sinusoidal endothelial C4d staining is more frequently observed in cross-match-positive recipients.…”
Section: Histological Findings In Liver Transplant Recipients With Domentioning
confidence: 99%
“…However, a definite diagnosis requires substantiation by DSA testing, diffuse C4d staining and the exclusion of other insults. Regarding "tissue injury pattern consistent with AMR", acute AMR resembles the histological findings for ischemic injury or biliary/vascular complications [19][20][21][22] , but little is known about AMR in patients with chronic allograft dysfunction. Regarding C4d positivity, its interpretation and practical utility in liver allografts is unclear and no consensus for the C4d pattern has been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Very few allografts fail because of acute cellular rejection (ACR) or AMR [35,36]. Recurrent disease, delayed manifestations of technical complications, such as vascular thrombosis or biliary sludge syndrome, and patient death are most commonly responsible for late (>1 year) graft failures [37,38].…”
Section: Failed Allograft Evaluationsmentioning
confidence: 99%